ПЛАНУВАННЯ ДІЯЛЬНОСТІ ГАЗОРОЗПОДІЛЬНИХ ПІДПРИЄМСТВ - Савка, Ю. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article deals with the peculiarities of activity of gas distribution enterprises. The influence of various factors on the process of planning on the given enterprises is studied. The distribution of functions among enterprises of the gas complex is investigated. The main features of gas distributing enterprises are distinguished, which in turn will influence the system of planning their activities. Some indicators of the activity of public stock company "Ivano-Frankivsk Gas" are investigated and the main problems in functioning of this enterprise are revealed. Also, the budget structure and its influence on the planning of the gas distribution enterprise are considered.